2016
DOI: 10.1002/cncy.21660
|View full text |Cite
|
Sign up to set email alerts
|

Young investigator challenge: Validation and optimization of immunohistochemistry protocols for use on cellient cell block specimens

Abstract: BACKGROUND:The objective of the current study was to establish a process for validating immunohistochemistry (IHC) protocols for use on the Cellient cell block (CCB) system. METHODS: Thirty antibodies were initially tested on CCBs using IHC protocols previously validated on formalin-fixed, paraffin-embedded tissue (FFPE). Cytology samples were split to generate thrombin cell blocks (TCB) and CCBs. IHC was performed in parallel. Antibody immunoreactivity was scored, and concordance or discordance in immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 17 publications
2
76
0
Order By: Relevance
“…Our second goal was to ascertain whether INSM1 staining in Cellient cell blocks prepared from cytologic samples correlates with corresponding surgical pathology specimens. Prior studies have compared immunohistochemical staining results in Cellient cell blocks and traditional cell blocks . Wagner et al reported identical staining in both types of cell blocks in 53% of cases, although staining in Cellient preparations had a lower intensity in 10% of the stains used.…”
Section: Discussionmentioning
confidence: 99%
“…Our second goal was to ascertain whether INSM1 staining in Cellient cell blocks prepared from cytologic samples correlates with corresponding surgical pathology specimens. Prior studies have compared immunohistochemical staining results in Cellient cell blocks and traditional cell blocks . Wagner et al reported identical staining in both types of cell blocks in 53% of cases, although staining in Cellient preparations had a lower intensity in 10% of the stains used.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated problems with validation in nearly one half of antibodies tested using the Cellient cell block system (fixed in PreservCyt). 9 The antibodies had been previously validated for formalin-fixed, paraffin-embedded specimens. These findings bring into question the utility of methanol-fixed material for ICC and the probable need for revalidation of antibodies when methanol-fixed material is used.…”
Section: Committee IVmentioning
confidence: 99%
“…A recent study has questioned the reliability of the use of immunocytochemistry on methanol-fixed cell block material. 9 …”
Section: Committee IVmentioning
confidence: 99%
“…All the illustration cases are processed this way. Nevertheless, our experience is similar to many other investigators in the necessity to adjust the protocols to the antibody in question and to the cytology material available (Sauter et al., 2016). …”
Section: Resultsmentioning
confidence: 99%